Cyberhooligans: a manifestação da violência das redes sociais - Bagni, Guilherme [UNESP] (2015)
Fans are a part of the sports context, and consequently generate influences on teams and athletes. Inside the fans group, there are some subdivisions, one of them are the organized fans. Although they are presented in many sports, this dissertation focuses on the soccer ones, whose actions, especially the violent ones, are a topic that is always on discussion as well as its relationship with soccer teams' board of directors. This relationship, however, is becoming weaken due to violent episodes. Besides that, the growth of social networks and its use by soccer organized fans, create an important mechanism to publicize its activities and to mark fights with other fans. Taking all these into consideration, this dissertation aims to analyze the official pages of some soccer organized fans on Facebook, to seek to categorize the content posted, to check for content related to the topic violence, to use the method of online content analysis, using techniques of nethnography and content analysis. The universe of this research was made up of Facebook fanpages of three differenet soccer organized fans' team of São Paulo city. We analyzed all the posts of these groups for the period of the year of 2014. For data analysis was used content analysis, which there was the categorization and prioritization of content and, after that, analysis and interpretation of data. The results are presented in percentage. We noted that the categories games, media and parties showed the most outstanding in relation to the overall outcome of the three organized fans analyzed. It was found out that the issue of violence happens in the background, as well as the club, which does not receive major highlight. Among the parties, that represent large number of the posts, we highlight the carnival, and we realized then, the existence of different subgroups within the organized fans. We understand that this work presents advances on this topic, especially in mapping...